Survey Nonresponse and the Distribution of Income - Korinek, Anton (World Bank, Washington, DC, 2012)
The authors examine the distributional implications of selective compliance in sample surveys, whereby households with different incomes are not equally likely to participate. They discuss poverty and inequality measurement implications for monotonically decreasing and inverted-U compliance-income relationships. The authors demonstrate that the latent income effect on the probability of compliance can be estimated from information on response rates across geographic areas. On implementing the method on the Current Population Survey for the United States, they find that the compliance probability falls monotonically as income rises. Correcting for non-response appreciably increases mean income and inequality, but has only a small impact on poverty incidence up to poverty lines common in the United States.